PELAKSANAAN PROGRAM CSR (COPORATE SOCIAL RESPONSIBILITY) PADA PT. PERTAMINA (PERSERO) LIRIK KABUPATEN INDRAGIRI HULU - Firmando, Herman; ", Ernawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The implementation of the CSR ( Coporate Social Responsibility ) at PT . Pertamina (Persero) Lirik Indragiri Hulu. This study aims to investigate the implementation of CSR ( Corporate Social Responsibility) and factors inhibiting the implementation of CSR (Corporate Social Responsibility) at PT . Pertamina EP Asset I Lirik Indragiri Hulu . This study used a qualitative research study descriptive data . subsequent to collect data using  interviews and observation authors as a means of collecting research data. After collecting data from informants research is Head of CSR PT . Pertamina, Head Lirik and Lirik  Area and Village Heads it is known that it can be seen that the implementation ofCorporate Social Responsibility conducted by PT Pertamina has been implemented in accordance with the provisions and social responsibility. But there are still shortcomings in the implementation of activities such as activities that are not effective and do not fit as well as the number of activities a bit. The limiting factors are the internal factors include the source of funds and human resources , and external factors that government policy as well as the support of the local community .Keywords : Program, Corporate Social Responsibility